The Mapping Fulfillment of National Education Standards and Relevance to the Learning’s Quality and Completeness of Learning in High School - Elisanti, Evi; Budiwan, Jauhan (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
This study aims to determine the profile of the fulfillment of national education standards and the results of national exams as well as learning media and the learning process in one of the senior high schools in the city of Kediri. The method used in this research is a survey method. Data collection techniques used were observation, questionnaires, and interviews. The results showed that the profile of the fulfillment of 8 National Education Standards in one of the public high schools in Kediri City with the highest gap in the standard process component of 2.38%, the standard of facilities and infrastructure of 1.43%, the standard of assessment of 1.43%, the standard of the content is 1.42% and the standard of education and teaching staff is 0.48%. The national exam score in one of the senior high schools in Kediri has an average of 5.14. Classroom learning activities are going well but not optimal with an average value of 79%. The value of fulfillment in the student's book, the value obtained is 63% and the value of deficiency is 37%. The value of fulfillment in the teacher's handbook obtained a value of 75% and a deficiency value of 25%. The results of national exams, media, and learning process activities provide information that can be used as a basis for conducting research activity.